Structural changes in the cruise network by ship size in Northeast Asia - Hirohito Ito; Shinya Hanaoka; Kashin Sugishita (Asian Journal of Shipping and Logistics (AJSL), 2022)
Several ports want cruise ships to call at their ports for economic benefits. However, the main cause of concern is the complexity of port selection behavior for cruise lines. Tracking cruise ship movement data may help them understand the port selection behavior of cruise lines. This study aimed to examine the structural changes in the cruise network by ship size in Northeast Asia from 2014 to 2019 using network science methods with automatic identification system data. We identified five key findings. First, the number of nodes and edges in the mega- and small-size ship networks was growing rapidly. Second, the small-size network was growing with unique characteristics of low density and average clustering coefficient, and high average shortest path length and diameter. Third, the hub ports of Shanghai in the mega- and Hiroshima and Kobe in the small-size had gained more degrees over time. Fourth, owing to the deployment of new mega-ships in Shanghai, existing large- and mid-ships were shifting to different ports. Finally, modularity of all sizes increased over time, and the community structure became clearer.
Keywords: 650; Automatic identification system data; Cruise network; Cruise ship size; Network science; Northeast Asia